2015
DOI: 10.1007/s13277-015-4367-1
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of FUT2 gene polymorphisms and environmental factors are associated with oral cancer risk

Abstract: In humans, fucosyltransferase-2 (FUT2) plays an important role in α1,2- linkage of fucose and participates in complex cellular processes such as fertilization, embryogenesis, and immune responses. However, little information is available concerning the FUT2 expression in tumorigenesis. The aim of this work was to investigate the combined effect of FUT2 gene polymorphisms and exposure to environmental carcinogens on the susceptibility and clinic pathological characteristics of oral cancer. Four SNPs of the FUT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…For example, increased expression of FUT1 has been associated with increased propensity to metastasize in melanoma and advanced stage in ovarian cancer, while downregulation of FUT1 in a HER2-positive breast cancer cell line decreased proliferation [92–94]. DNA variants in FUT2 has been associated with increased risk of oral cancer in individuals who smoke and/or chew betel quid while in pancreatic cancer, secretor status was not associated with risk [95,96]. In an evaluation of variants within FUT loci variants within FUT2 and FUT3 were associated with interstinal- and diffuse-type gastric cancer, respectively [97].…”
Section: Modification Of Abo Phenotypesmentioning
confidence: 99%
“…For example, increased expression of FUT1 has been associated with increased propensity to metastasize in melanoma and advanced stage in ovarian cancer, while downregulation of FUT1 in a HER2-positive breast cancer cell line decreased proliferation [92–94]. DNA variants in FUT2 has been associated with increased risk of oral cancer in individuals who smoke and/or chew betel quid while in pancreatic cancer, secretor status was not associated with risk [95,96]. In an evaluation of variants within FUT loci variants within FUT2 and FUT3 were associated with interstinal- and diffuse-type gastric cancer, respectively [97].…”
Section: Modification Of Abo Phenotypesmentioning
confidence: 99%
“…The association of rs1047781 with cancer antigen 19-9 (CA19-9) levels and carcinoembryonic antigen (CEA) concentration in esophageal squamous cell cancer and pancreatic cancer also was confirmed by genome-wide association studies 16 . Moreover, our previously study also shown that interactions of FUT2 polymorphisms with betel quid chewing habits maybe altering oral cancer susceptibility 17 . However, the effects of FUT2 polymorphisms are still unclear in HCC.…”
Section: Introductionmentioning
confidence: 81%
“…Allelic discrimination of the FUT2 polymorphisms rs281377, rs1047781, rs601338, and rs602662 was assessed using an ABI StepOne Real-Time PCR System (Applied Biosystems), SDS v3.0 software (Applied Biosystems), and the TaqMan assay 17 - 19 . The final volume for each reaction was 5 μL, containing 2.5 μL TaqMan Genotyping Master Mix, 0.125 μL TaqMan probes mix, and 10 ng genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Genes such as ALDOB (aldolase, fructose-bisphosphate B) [68], KHK (ketohexokinase) [69], CHRNA7 [70], GSTA3 [71], APOA1 [72], CEBPA (CCAAT enhancer binding protein alpha) [73], PCK1 [74], ATP1A1 [75], CLCA1 [76], EMB (embigin) [77], SLC22A18 [78], FUT5 [79] and ITLN1 [80] were linked with progression of various cancer types, but these genes might be identified with growth of NET. Polymorphic genes such as GSTA1 [81], GSTA2 [82], MGST1 [83], NAT2 [84], SULT1A2 [85], SULT2A1 [86], UGT1A6 [87], UGT2B15 [88], UGT2B17 [89], ABCC2 [90], FUT2 [91] and APOB (apolipoprotein B) [92] were liable for progression of various cancer types, but these polymorphic genes might be diagnosed with growth of NET. Genes such as G6PC [93] and SGK1 [94] were associated with proliferation of various cancer cells types, but these gene might be linked with proliferation of NET cells.…”
Section: Discussionmentioning
confidence: 99%